Full Gamut Wall Tunability from Persistent Micelle Templates via Ex Situ Hydrolysis. Issue 18 (28th March 2019) - Lantz, Kayla A.; Clamp, Nicholas Blake; van den Bergh, Wessel; Sarkar, Amrita; Stefik, Morgan
Abstract: The predictive self‐assembly of tunable nanostructures is of great utility for broad nanomaterial investigations and applications. The use of equilibrium‐based approaches however prevents independent feature size control. Kinetic‐controlled methods such as persistent micelle templates (PMTs) overcome this limitation and maintain constant pore size by imposing a large thermodynamic barrier to chain exchange. Thus, the wall thickness is independently adjusted via addition of material precursors to PMTs. Prior PMT demonstrations added water‐reactive material precursors directly to aqueous micelle solutions. That approach depletes the thermodynamic barrier to chain exchange and thus limits the amount of material added under PMT‐control. Here, an ex situ hydrolysis method is developed for TiO2 that mitigates this depletion of water and nearly decouples materials chemistry from micelle control. This enables the widest reported PMT range (M:T = 1.6–4.0), spanning the gamut from sparse walls to nearly isolated pores with ≈2 Å precision adjustment. This high‐resolution nanomaterial series exhibits monotonic trends where PMT confinement within increasing wall‐thickness leads to larger crystallites and an increasing extent of lithiation, reaching Li0.66 TiO2 . The increasing extent of lithiation with increasing anatase crystallite dimensions is attributed to the size‐dependent strain mismatch of anatase and bronze polymorph mixtures. Abstract : Persistent micelle templates (PMTs) use kinetic‐control to overcome the limitations of equilibrium‐based self‐assembly. A new ex situ sol process enables PMT sample series with constant pore size and ≈2 Å precision adjustment of the wall‐thickness, spanning the gamut from sparse walls to nearly isolated pores. The resulting isomorphic series demonstrates tunable confinement effects upon lithium ion intercalation.